The Bleye Kukum of South Upi: The Justice System on Conflict Resolution - Tahir Salipada; Datuali Abdula; Marop Kanakan (RIRAI Publisher, 2022)
This study aimed to assess the level of effectiveness of the implementation of the Bleye Kukum justice system in terms of: Conflict resolution, Peace and Order, Governance, and Economy was also identified. Also, the problems encountered by the Indigenous People concerning the Bleye Kukum justice system, which was the basis of the policy recommendations. The study used the descriptive-evaluative method to determine the level of effectiveness of the implementation of the Bleye Kukum justice system in South Upi, Maguindanao. It was conducted in the selected barangays in the municipality of South Upi, Maguindanao. The respondents of this study were the Tri-People (Muslim, Christian and Teduray) living in the selected barangays which are Barangay Romongaob and Barangay Kuya with the total of One Hundred (100) respondents. The findings show that the respondents’ profile revealed that in terms of the profile of the respondents, most of the respondents were belong to the age of 30 to 39, married, female, earning of 3,000 and below per month, with a big number of dependents and have elementary level of educational attainment. In the level of effectiveness of the implementation of the Bleye Kukum Justice System in terms of conflict resolution, peace and order, governance and economy were considered as effective. Majority of the respondents experienced problem on the Bleye Kukum’s process of settling. Thus, it is concluded that the level of effectiveness of the implementation of the Bleye Kukum Justice System is effective.